Value-Based Payment System and Consideration of Radiology - Choong Wook Lee (Journal of the Korean Society of Radiology)
The value-based payment (VBP) system aims to improve the quality of healthcare while enhancing cost-efficiency, delivering better patient outcomes without increasing overall healthcare costs. It has been proposed as an alternative payment system to help sustain national insurance systems in response to the social and economic challenges posed by rising healthcare expenditures. Radiology plays a crucial role in disease prevention, diagnosis, and treatment; however, it is often undervalued. This review explores how radiology can be fully recognized for its inherent value in the VBP system and continue to enhance patient outcomes and societal value.